1963
DOI: 10.1002/food.19630070808
|View full text |Cite
|
Sign up to set email alerts
|

Zum Tocopherolgehalt einiger Fette und Öle. 3. Mitt. Papyrographische Analyse einiger ungarischer Öle

Abstract: Zum Tocopherolgehalt einiger Fette und Ole. 3. Mitt.' Papyrographische Analyse einiger ungarischer ole K. TAUFEL uud R. SERZISKO~ Zur Erweiterung unserer Kenntnisse iiber das natiirliche Vorkommen von Tocopherolen nach ihrer Menge unter Differenzierung auf die beteiligten Homologen ist eine Reihe von rohen Pflanzenolen ungarischer Provenienz3 untersucht worden, woriiber im folgenden berichtet wird. Die praparative Vorbereitung der Proben sowie die auf papyrographischem Wege durchgefuhrten Analysen bedienen sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1965
1965
1976
1976

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…That difference is also supported by evidence from the literature. Slover et al (1969) reported that atocopherol was the principal tocopherol in almond oil (total tocopherol content was 334 µg/g of oil), while Táufel and Serzisko (1963) found that 7-tocopherol was the principal tocopherol in apricot oil (total tocopherol content was 711 µg/g of oil).…”
mentioning
confidence: 99%
“…That difference is also supported by evidence from the literature. Slover et al (1969) reported that atocopherol was the principal tocopherol in almond oil (total tocopherol content was 334 µg/g of oil), while Táufel and Serzisko (1963) found that 7-tocopherol was the principal tocopherol in apricot oil (total tocopherol content was 711 µg/g of oil).…”
mentioning
confidence: 99%